Development Of Basic Gymnastics Course Textbooks For Students Of Physical Education Study Program - Citra Azhariat Malasari; Pasha Erik Juntara (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this research is to develop coursebooks for basic gymnastics courses for students of the Physical Education Study Program, Muhammadiyah University Kotabumi. This research method uses the Borg and Gall development procedure which consists of 10 steps. But in this research development research does not use all of it but only with 7 steps, that is: 1) needs analysis, 2) product manufacture, 3) product validation, 4) small group trials, 5) product revision stage I, 6) large group trials, 7) product revision stage II. The result of this study are the results of the validation of material experts with the overall validation mean of 87.85%, validation results from media and design experts with a minimum score of 27, maximum score of 108, the result score is 97 with a percentage of 89.81%, Results of the Assessment Phase I Trial (small group) with a percentage of 91.11%, Results of the Phase II Trial Assessment (large group) with a percentage result of 81.08%. Based on the result of data analysis, it can be concluded that the basic gymnastics textbook product is suitable for use by students of the FKIP UMKO physical education study program.